Problemáticas da questão moral em Crime e Castigo - Prudente, Sérgio Eduardo Lima (2010)
This research aims at investigating, from the novel Crime and Punishment, some aspects of the close relationship between moral and impulses to breaching the law. For this purpose, some psychoanalysis theory was used, predominantly from Freud and Lacan, and dialogues with philosophers, mainly Sade, Kant and Nietzsche. Through the main character of the novel, Raskolnikóv, and his history, whose most important point is a murder, some of the main themes are approached: the relation among the principle of pleasure and moral and action, the practical/rational argument of moral, the split of moral experience, the distortion of reason as a way to releasing of destructive impulses and, finally, it is still seen an exit through love. We start presenting the perspectives of the study, a brief theory of the crime in the Freudian theory and the issue of ethics and moral. Later, on the chapter about Crime and Punishment, the presentation of the novel and its author is made through narrowing down the general aspects of Russia in the end of the 19th century, heading towards biographical information of Dostoiévski and his work up to sections of elements from the book. On this paper, there are two other psychoanalytical readings of the same work, with their respective criticisms